An Ox and a Hut: Notes on an Uruk-Period Cylinder Seal - Lassen, Agnete W. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2021)
BC.038200 (NBC 12116) is a light-brown stone cylinder seal measuring 24 x 16 mm, showing an ox approaching an architectural structure. It was presented as a gift to Yale University by William David and Olga Draiggs of Fort Lauderdale in 2017. W. David acquired it in 1969 through inheritance from his father, the antiquities dealer Elias Solomon David (b. 1891) along with the rest of the unsold stock. Born in Baghdad, E.S. David moved to Paris in 1904 where he became acquainted with père Jean-Vincent Scheil, the French Dominican scholar and Assyriologist, who kindled E.S. David’s interest in cuneiform (personal communication, W. David 2016). In 1914, E.S. David moved to the USA, where he found his primary market. He was active in the art trade between c. 1910 until shortly before his death in 1969 and became one of the main dealers in ancient Iraqi art and artifacts in the USA in the 20th century. The cuneiform documents left in his stock after his death in 1969 were sold at Christie’s, New York in 2015, Sale 3748. 360 West Asian stamp and cylinder seals dating from the Uruk to Sasanian periods, including BC.038200, were gifted to Yale University by his son two years later.